Tubo-ovarian abscess in a virgin girl - Giti Iravanlo; Iraj Harirchi; Tahere Ashrafganjooei (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: Tubo-ovarian abscess as a serious complication of pelvic inflammatory disease is very uncommon in sexually inactive girls.Case: We report a case of tubo-ovarian abscess in a 24-year-old sexually inactive girl with transverse vaginal septum who was presented with abdominal pain and a pelvic mass and without prior surgical history and no evidences of appendicitis, inflammatory bowel disease, or cancer. A huge unilateral tubo-ovarian abscess was recognized at laparotomy. Unilateral salpingoophorectomy, hysterectomy and postoperative antibiotic therapy cured the patient.Conclusion: Early diagnosis and treatment are essential to prevent further sequel including infertility, ectopic pregnancy, and chronic pelvic pain which cause morbidity